First Fruits of Prayer: A Forty-Day Journey Through the Canon of St. Andrew - Plekon, Michael (Cistercian studies quarterly, 2006)
The article reviews the book "First Fruits of Prayer: A Forty-Day Journey Through the Canon of St. Andrew," by Frederica Mathewes-Green.